IOT Driven Smart Chair for Posture and Health Monitoring - Arthi M,; Dr. J. Savitha M.Sc., M.Phil., Ph.D, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Poor sitting and posture have emerged as serious health issues, contributing to musculoskeletal disorders, backache, and other medical complications. In response to these problems, this paper proposes an IoT-Driven Smart Chair for Posture and Health Monitoring aimed at improving ergonomics and user wellness. The system incorporates ESP32 microcontroller-based sensors to regularly check for posture deviations as well as monitor essential health measures, such as Body Mass Index (BMI), heart rate, blood pressure, and blood oxygen (SPO2) levels. Using IoT technology, the intelligent chair gathers real-time data and processes it using ESP32, giving instant feedback in the form of auditory or visual signals to prompt corrective behaviour. The collected health measurements are sent to a cloud-based platform for analysis and storage. A web-based interface developed using PHP enables users to monitor their health patterns, view personalized reports, and observe posture status over time. This solution finds its greatest usefulness in sedentary work settings, were poor posture and inactivity lead to long-term health problems. By combining real-time posture correction, health monitoring, and data-driven recommendations, the proposed system will act as a preventive healthcare system. Future developments could involve machine learning models for personalized advice and wearable device integration to make it more accurate and efficient. This study emphasizes the capability of IoT in ergonomic healthcare solutions, providing an intelligent and anticipatory solution for proper posture and overall well-being.
Keywords: Poor sitting; posture; Health Monitoring; ergonomics